Answer:
y=x-6 (1)
make y the subject of the equation (1)
make y the subject of the equation (1)y=x-6 (3)
make y the subject of the equation (1)y=x-6 (3)substitute y=x-6 for y in equation 2
make y the subject of the equation (1)y=x-6 (3)substitute y=x-6 for y in equation 2y=2x-8 (2)
make y the subject of the equation (1)y=x-6 (3)substitute y=x-6 for y in equation 2y=2x-8 (2)y(x-6)=2x-8
make y the subject of the equation (1)y=x-6 (3)substitute y=x-6 for y in equation 2y=2x-8 (2)y(x-6)=2x-8x-6=2x-8
make y the subject of the equation (1)y=x-6 (3)substitute y=x-6 for y in equation 2y=2x-8 (2)y(x-6)=2x-8x-6=2x-8collect like terms
make y the subject of the equation (1)y=x-6 (3)substitute y=x-6 for y in equation 2y=2x-8 (2)y(x-6)=2x-8x-6=2x-8collect like terms8-6=2x-x
make y the subject of the equation (1)y=x-6 (3)substitute y=x-6 for y in equation 2y=2x-8 (2)y(x-6)=2x-8x-6=2x-8collect like terms8-6=2x-xx=2.
make y the subject of the equation (1)y=x-6 (3)substitute y=x-6 for y in equation 2y=2x-8 (2)y(x-6)=2x-8x-6=2x-8collect like terms8-6=2x-xx=2.substitute x=2 in equation 3
make y the subject of the equation (1)y=x-6 (3)substitute y=x-6 for y in equation 2y=2x-8 (2)y(x-6)=2x-8x-6=2x-8collect like terms8-6=2x-xx=2.substitute x=2 in equation 3y=x(2)-6
make y the subject of the equation (1)y=x-6 (3)substitute y=x-6 for y in equation 2y=2x-8 (2)y(x-6)=2x-8x-6=2x-8collect like terms8-6=2x-xx=2.substitute x=2 in equation 3y=x(2)-6y=2-6
make y the subject of the equation (1)y=x-6 (3)substitute y=x-6 for y in equation 2y=2x-8 (2)y(x-6)=2x-8x-6=2x-8collect like terms8-6=2x-xx=2.substitute x=2 in equation 3y=x(2)-6y=2-6y= -4
make y the subject of the equation (1)y=x-6 (3)substitute y=x-6 for y in equation 2y=2x-8 (2)y(x-6)=2x-8x-6=2x-8collect like terms8-6=2x-xx=2.substitute x=2 in equation 3y=x(2)-6y=2-6y= -4therefore x=2 and y= -4